2017
DOI: 10.1002/ajpa.23335
|View full text |Cite|
|
Sign up to set email alerts
|

Infanticide in chimpanzees: Taphonomic case studies from Gombe

Abstract: The cases described here suggest that chimpanzees may not always completely consume infanticide victims, while reports on chimpanzee predation indicated that complete consumption of monkey prey usually occurred. Infanticidal chimpanzees undoubtedly gain nutritional benefits when they consume dead infants, but this benefit may not sufficiently explain infanticide in this species. Continued study of infanticidal and hunting behavior, including skeletal analysis, is likely to be of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Most reports concern infants of 'stranger' females getting killed and eaten, but intra-group cases also occur [79]. The rate of post-infanticide cannibalism is higher in chimpanzees than other species of nonhuman primates [80]; a review of 40 cases revealed that 23% of chimpanzee infanticide victims were consumed wholly, and another 37.5% partially [81].…”
Section: (B) Conspecifics: Cannibalismmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reports concern infants of 'stranger' females getting killed and eaten, but intra-group cases also occur [79]. The rate of post-infanticide cannibalism is higher in chimpanzees than other species of nonhuman primates [80]; a review of 40 cases revealed that 23% of chimpanzee infanticide victims were consumed wholly, and another 37.5% partially [81].…”
Section: (B) Conspecifics: Cannibalismmentioning
confidence: 99%
“…B 373: 20170257 with similar-sized monkey prey [81], suggesting a psychological difference between eating a conspecific and another species. Third, intra-community infants are eaten less completely than extra-community infants [81]. The psychology of cannibalism in chimpanzees requires further study.…”
Section: Questions For Future Research and Conclusionmentioning
confidence: 99%
“…A comparison between Sonso and Kasakela (Gombe) supports the idea of a by-product explanation: Sonso chimpanzees are relatively poor hunters, even though historically low levels (Newton-Fisher et al 2002) have risen in recent years (Hobaiter et al 2017), whereas Kasakela chimpanzees hunt more frequently (Stanford et al 1994;Gilby et al 2006). Cannibalism is low for Sonso, but in Kasakela, all of the victims of infanticide are cannibalized, at least in part (infanticide victims are eaten less completely than prey items: Kirchhoff et al 2018). Thus, chimpanzees accustomed to eating meat appear more likely to consider the victims of infanticide as a suitable food-they may have more of a generalized 'taste for meat'.…”
Section: Discussionmentioning
confidence: 75%
“…Cannibalism is well documented in infanticide cases (Goodall 1977;Takahata 1985;Newton-Fisher 1999;Watts and Mitani 2000;Walker et al 2018a;Kirchhoff et al 2018;Nishie and Nakamura 2018), and is the norm in at least two populations (12 of 14 within-group incidences in the Kanyawara community, Kibale, Uganda: Arcadi and Wrangham 1999, and all cases in which the infanticide was successful at Gombe, Tanzania: Murray et al 2007). However, infanticide victims at Gombe (the only site for which published data exist) tend to be exploited less fully than prey animals, with less nutritionally rich areas (such as hands and feet, rather than organs or large muscle groups) more likely to be eaten (Kirchhoff et al 2018). Infanticide without cannibalism has also been reported, including at Budongo (Arcadi and Wrangham 1999;Townsend et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility that another chimpanzee may have inflicted these tooth marks could not be evaluated using tooth mark measurement data. While wild chimpanzee taphonomic damage on much smaller primates as a result of predation (Plummer & Stanford, ; Pobiner, DeSilva, Sanders, & Mitani, ), and taphonomic damage resulting from chimpanzee infanticide (Kirchhoff et al, ) have been described, there are currently no published measurements of chimpanzee tooth marks on the skeletal remains of other adult chimpanzees. Jurmain (, ) reported tooth marks on chimpanzee skeletal remains made by other chimpanzees, but with relatively limited documentation.…”
Section: Discussionmentioning
confidence: 99%